The Charter of Fundamental Rights of the European Union and the employment relation (Oxford, 2019)
"The Charter of Fundamental Rights of the European Union is the most developed and comprehensive legally binding human rights instrument in the social field of the European Union. It is becoming increasingly important and is the first instrument that includes both civil and political rights on one hand and social rights on the other. Despite this, the Court of Justice of the European Union has only rarely dealt with fundamental social rights. In this context, employment rights need to be examined in this new rights framework. Following on from previous volumes setting out links between European labour law and fundamental social rights (as enshrined in relevant UN, ILO and Council of Europe instruments), in this book the ETUI Transnational Trade Union Rights (TTUR) Expert Network examines the justiciability of social rights and critically analyses the effectiveness of those rights embodied in the EU Charter.